PENGUJIAN GA3 DAN RASIO TANAM TETUA TERHADAP PRODUKSI BENIH HIBRIDA HIPA 14 MELALUI RANCANGAN PETAK TERBAGI - Mulsanti, Indria Wahyu; Widyastuti, Yuni; Satoto, nFN (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2017)
The three lines methods in hybrid rice have disadvantages in seed production procedures that result in low seed yield. Low levels of natural crosses (outcrossing) is one of the causes of low seed yield in hybrid seed production. GA3 application and proper spacing , expected to improve of F1 hybrid seed production. The experimental design used was Split Plot design with three replications. The main plot was doses of GA3 application consist of 0, 200 ppm and 300 ppm. The subplot was row ratios of restores:CMS i,e 2R:8A, 2R:12A; 2R:16A. The material used is parental lines of HIPA 14. The results showed that GA3 application was able to increased plant height of parental lines (CMS and restorer), number of productive tillers, exterted panicle and stigma also outcrossing rate at seed production of HIPA 14. The row ratio was influenced for plant heigh of CMS lines. Interaction between GA3 and row ratio was increased plant height of parental lines, exerted panicle, and outcrossing rate